i need some help

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions.

- anonymous

i need some help

- jamiebookeater

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions

- anonymous

##### 1 Attachment

- IrishBoy123

|dw:1441715548469:dw|

- IrishBoy123

have you got your equation for \(f^{-1}(x)\) yet??

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- anonymous

idk how to do anything with it my teacher never taught me how

- IrishBoy123

first, we'll re-write your equation as y = 2x - 6, so this takes in x values and returns y values
now switch that around so that it says x = ... ie give me an equation that takes in y values and returns x values
[you'll see what the point of this is when we're done]

- anonymous

so takes in is the 2x-6 part and puts out is y=

- IrishBoy123

yes
now switch it around so it says x = ....

- IrishBoy123

example
y = 2x +1
x = y/2 - 1/2

- IrishBoy123

example
y = 9x - 3
x = (1/9) (y+3)

- anonymous

y-1/2=x

- IrishBoy123

example
i start with y = 2x +1
i switch around to get x = y/2 - 1/2
example
i start with y = 9x - 3
i switch around to get x = (1/9) (y+3)
you are starting with y = 2x - 6
can you switch it around in same way?

- IrishBoy123

you can do it!

- IrishBoy123

i can do the first example is steps, if that helps??!!

- anonymous

x=y/2-2/1

- IrishBoy123

??

- anonymous

idk im lost

- anonymous

thats what i thought

- IrishBoy123

x=y/2-2/1
for you question?!?!?

- anonymous

yes

- IrishBoy123

i'll try this
1st example
\(y = 2x +1\)
add -1 to each side
\(y-1 = 2x +1-1\)
so
\(y-1 = 2x\)
divide each side by 2
\(y/2-1/2 = 2x/2\)
so
\(y/2-1/2 = x\)
just switch left hand and right hand sides around
\(x = y/2-1/2\)
and that is done

- anonymous

and thats what u want me to find for my prob

- IrishBoy123

2nd example
\(y = 9x - 3\)
add 3 to each side
\(y +3= 9x - 3+3\)
so
\(y +3= 9x \)
divide each side by 9
\((1/9)(y +3)= 9x/9\)
so
\((1/9)(y +3)= x\)
switch around
\(x=(1/9)(y +3)\)

- IrishBoy123

yes
if you truly have not been shown how to do this algebra, then you should really not be trying to do inverse functions...

- anonymous

i must have missed that class but yeah

- IrishBoy123

well copy what i did and see how you go.

- anonymous

x=(y/2)+(2/6)

- IrishBoy123

very good
we can simplify a little, ie the 2/6, right?

- anonymous

yes
3

- anonymous

what happens now

- IrishBoy123

i'll do this bit as it's just notation, important notation but you havealready done the hard bit
you recall we took your function
\( f(x) = 2x - 6\)
and re-wrote as \( y = 2x - 6\) so we could manipulate it a bit easier
well we now take your solution for the inverse
ie \( x=y/2+3\)
and we re-write it as
\(f^{-1}(x) =x/2 + 3 \)
so or example \(f(3) = 0\), and hey presto \(f^{-1}(0) = 3\)!!!
so you now take \(f^{-1}(x) =x/2 + 3 \) and answer the question

- IrishBoy123

they want \(f^{-1}(2)\)

- anonymous

alright i followed and understood upto f(3)=0 and then i got lost

- IrishBoy123

no worries
function
\(f(x) = 2x - 6 = 0 \implies f(3) = 2(3) - 6 = 0\)
inverse function
\(f^{-1}(x) = x/2 + 3 \implies f^{-1}(0) = 0/2 + 3 = 3\)!!
so we have function f and its inverse \(f^{-1}\). they reverse each other
plugging into \(f^{-1}(x) = x/2 + 3\) for x = 2
\(f^{-1}(2) = (2)/2 + 3\)

- anonymous

okay i think i get it

- anonymous

so doo i solve f−1(2)=(2)/2+3

- IrishBoy123

yes

- anonymous

f=1/2

- anonymous

no thats wrong

- IrishBoy123

yes, go again

- anonymous

5

- anonymous

-5

- IrishBoy123

\[f^{-1}(2) = \frac{(2)}{2} + 3\]

- anonymous

im lost a little

- anonymous

what do i do with f^-1(2)

- anonymous

so i just solve the answer part

- IrishBoy123

|dw:1441720473828:dw|

- IrishBoy123

yes
just solve

- anonymous

f−1(2)=4

- IrishBoy123

indeed

- anonymous

thats my answer

- IrishBoy123

yes

- anonymous

okay

Looking for something else?

Not the answer you are looking for? Search for more explanations.